The “indirect legislative power” of constitutional judge (2013)
The separation of powers is one of the most important characteristics of modern constitutionalism, which seeks to protect the State against tyrannical Governments. Although it is certain that the separation of powers gives autonomy to each one of these (executive, legislative and judicial), it does not imply that it may arise some form for supplementing the function of a power to other, so here we remit, in terms of the legislative and Judicial (Constitutional) powers, to the manipulative sentences and more exactly to additive or integrative sentences, that are those able to protect the Constitution and complement the legislative work.